2017
DOI: 10.1038/s41598-017-04487-x
|View full text |Cite
|
Sign up to set email alerts
|

0404 inhibits hepatocellular carcinoma through a p53/miR-34a/SIRT1 positive feedback loop

Abstract: DNA-damaging agents have been used in cancer chemotherapy for a long history. Unfortunately, chemotherapeutic treatment strategies against hepatocellular carcinoma (HCC) are still ineffective. We screened a novel DNA-damaging compound, designated as 0404, by using time-dependent cellular response profiling (TCRP) based on unique DNA-damage characteristics. We used human HCC cell lines and HCC xenograft mouse model to analyze the anti-cancer effects of 0404. Transcriptome and miRNA arrays were used to verify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Previous research showed that TP53 had the highest prevalence of protein-altering mutations in HCC [37,38]. Several studies have shown that tumor drugs can suppress the proliferation of liver cancer cells by activating the P53/miR-34a/SIRT1 positive feedback loop [39,35]. In our study, we show that the P53/miR-34a/SIRT1 positive feedback loop is de cient in the P53-de cient Hep3B and P53-mutated Huh7 cell lines.…”
Section: Discussionsupporting
confidence: 61%
“…Previous research showed that TP53 had the highest prevalence of protein-altering mutations in HCC [37,38]. Several studies have shown that tumor drugs can suppress the proliferation of liver cancer cells by activating the P53/miR-34a/SIRT1 positive feedback loop [39,35]. In our study, we show that the P53/miR-34a/SIRT1 positive feedback loop is de cient in the P53-de cient Hep3B and P53-mutated Huh7 cell lines.…”
Section: Discussionsupporting
confidence: 61%
“…Ito et al found that miR-34a increased with age in endothelial cells in senescent human umbilical cord vein endothelial cells and in the hearts and spleens of older mice [ 31 ]. The regulation of miR-34a-5p/SIRT 1 pathway was investigated in multiple disease and aging models for its effect on aging and oxidative damage [ 33 35 ]. In the present research, our data demonstrated that the expression level of miR-34a-5p in the oxidized HLE-B3 cells is 2.59 fold higher compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As a key factor in inhibiting tumour formation, the p53 gene may be either wild-type or mutant type. The wild-type p53 gene may act as a tumour suppressor gene by repairing damaged DNA, blocking cell cycle, inhibiting cell proliferation and promoting apoptosis (31)(32)(33)(34). However, the mutant-type p53 promotes cell proliferation through negative regulation of the wild-type p53 protein, thereby protecting cells from apoptosis and promoting tumour development.…”
Section: Discussionmentioning
confidence: 99%